Anticoagulation for the Pregnant Patient with a Mechanical Heart Valve, No Perfect Therapy: Review of Guidelines for Anticoagulation in the Pregnant Patient. (22nd November 2017) - Richardson, Aaron; Shah, Stuart; Harris, Ciel; McCulloch, Garry; Antoun, Patrick
Abstract : Heart valve replacement with a mechanical valve requires lifelong anticoagulation. Guidelines currently recommend using a vitamin K antagonist (VKA) such as warfarin. Given the teratogenic effects of VKAs, it is often favorable to switch to heparin-derived therapies in pregnant patients since they do not cross the placenta. However, these therapies are known to be less effective anticoagulants subjecting the pregnant patient to a higher chance of a thrombotic event. Guidelines currently recommend pregnant women requiring more than 5 mg a day of warfarin be switched to alternative therapy during the first trimester. This case report highlights a patient who was switched to alternative therapy during her first pregnancy and suffered a devastating cerebrovascular accident (CVA). Further complicating her situation was during a subsequent pregnancy; this patient continued warfarin use during the first trimester and experienced multiple transient ischemic attacks (TIAs). This case highlights the increased risk of thrombotic events in pregnant patients with mechanical valves. It also highlights the difficulty of providing appropriate anticoagulation for the pregnant patient who has experienced thrombotic events on multiple anticoagulants.